2021
DOI: 10.1039/d0sc03381b
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of annihilators for triplet–triplet annihilation upconversion via auxiliary-field quantum Monte Carlo

Abstract: Electronic structure theories such as AFQMC can accurately predict the low-lying excited state energetics of organic chromophores involved in triplet–triplet annihilation upconversion. A novel class of benzothiadiazole annihilators is discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 97 publications
(133 reference statements)
0
19
0
Order By: Relevance
“…Recent technical advances, including vastly improved efficiency for multideterminantal trial wavefunctions, 23,51 utilization of correlated sampling (CS) in the Monte Carlo protocol to directly compute energy differences, 52 and implementation on GPU hardware, 23,53 has made it feasible to treat significantly larger systems. [54][55][56] Ref. 51 is recommended as a good introduction to the theory of AFQMC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent technical advances, including vastly improved efficiency for multideterminantal trial wavefunctions, 23,51 utilization of correlated sampling (CS) in the Monte Carlo protocol to directly compute energy differences, 52 and implementation on GPU hardware, 23,53 has made it feasible to treat significantly larger systems. [54][55][56] Ref. 51 is recommended as a good introduction to the theory of AFQMC.…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by overcoming significant challenges arising from the greater size and complexity of the metallocene series (as compared to molecules in earlier publications). 23,29,55,56,73 For example, prior work 55 has demonstrated that it is essential to employ an appropriate multiconfigurational trial wavefunction, since calculations based on Hartree-Fock (HF) trial wavefunctions did not reliably lead to chemically accurate results for these systems. Deployment of an appropriate multiconfigurational trial wavefunction in the application of the AFQMC approach to transition metal containing systems remains essential if one is aiming at robust, benchmark quality results.…”
Section: Introductionmentioning
confidence: 99%
“…Recent technical advances, including vastly improved efficiency for multideterminantal trial wavefunctions, 23,50 utilization of correlated sampling (CS) in the Monte Carlo protocol to directly compute energy differences, 51 and implementation on GPU hardware, 23,52 has made it feasible to treat significantly larger systems. [53][54][55] These advances have allowed systematic studies of three classes of small transition metal containing species (atoms, diatomic molecules, and tetrahedral, square planar, or octahedral complexes containing simple small molecule ligands) with highly encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by overcoming significant challenges arising from the greater size and complexity of the metallocene series (as compared to molecules in earlier publications). 23,29,54,55,70 Prior work 54 has demonstrated that it is essential to employ an appropriate multiconfigurational trial wavefunction; calculations based on a single determinant (mainly UHF) trial sometimes yield energy differences comparable to DFT for these systems. Deployment of an appropriate multiconfigurational trial function in the application of the AFQMC approach to transition metal containing systems remains essential if one is aiming at robust, benchmark quality results.…”
Section: Introductionmentioning
confidence: 99%
“…Recent technical advances, including vastly improved efficiency for multideterminantal trial wavefunctions, 23,50 utilization of correlated sampling (CS) in the Monte Carlo protocol to directly compute energy differences, 51 and implementation on GPU hardware, 23,52 has made it feasible to treat significantly larger systems. [53][54][55] These advances have allowed systematic studies of three classes of small transition metal containing species (atoms, diatomic molecules, and 4-6 coordinate complexes containing simple small molecule ligands) with highly encouraging results. Atomic ionization potentials, 23 diatomic bond energies, 29 and complex ligand dissociation energies, 54 have all been computed with a MAE of less than 1.5 kcal/mol across relatively large experimental gas phase data sets.…”
Section: Introductionmentioning
confidence: 99%